2015
DOI: 10.1016/j.renene.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The cumulative impact of tidal stream turbine arrays on sediment transport in the Pentland Firth

Abstract: a b s t r a c tThis contribution investigates the impact of the deployment of tidal stream turbine arrays on sediment dynamics and seabed morphology in the Pentland Firth, Scotland. The Pentland Firth is arguably the premier tidal stream site in the world and engineering developments are progressing rapidly. Therefore understanding and minimising impacts is vital to ensure the successful development of this nascent industry. Here a 3 dimensional coupled hydrodynamic and sediment transport numerical model is us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 54 publications
(51 reference statements)
3
57
0
Order By: Relevance
“…Changes to hydrodynamic regime can lead to second-order effects. Researchers have also investigated impacts on sediment transport and associated changes to morphology [32][33][34][35]. Wave-current interactions [36] can also be an important process, both in affecting the tidal resource and the changes to currents impacting the wave climate [37][38][39], the water quality [40] or aquatic organisms.…”
Section: Coastal Area Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes to hydrodynamic regime can lead to second-order effects. Researchers have also investigated impacts on sediment transport and associated changes to morphology [32][33][34][35]. Wave-current interactions [36] can also be an important process, both in affecting the tidal resource and the changes to currents impacting the wave climate [37][38][39], the water quality [40] or aquatic organisms.…”
Section: Coastal Area Modellingmentioning
confidence: 99%
“…The value used is often based on actuator disk theory with correction factors applied when array scale extraction is considered [43,44]. In three-dimensional models, such an approach would give unrealistic vertical velocity profiles, and thus, an additional sink term must be introduced to the model [35]. A review of the commonly-used methods is presented in [45].…”
Section: Coastal Area Modellingmentioning
confidence: 99%
“…Their study, however, was undertaken using a two-dimensional, depth-averaged model, which cannot resolve the specific near-bed velocity relevant for sediment transport processes; in particular, the potential exists for flow to be accelerated beneath tidal turbines, as well as around the sides, and this process clearly cannot be simulated with a depth-averaged model. A further study using a three-dimensional (3D) model, by Fairley et al [9], extended the modelled sediment transport in the Pentland Firth into predictions of bed level changes, and again investigated the possible effects of turbines deployed in the Inner Sound on sediment deposition and erosion. They found that currently proposed arrays would have only minimal effect on the baseline morphodynamics of the large sandbanks in the region, but did not consider the smaller sandbanks local to the arrays.…”
Section: Introductionmentioning
confidence: 99%
“…Martin-Short et al [8] and Fairley et al [9] both noted that accurate sediment modelling is inhibited by a lack of detailed knowledge of local sediment deposits and transport in the area. Fairley et al [9] combined a variety of data to construct a map of sediment type through the Pentland Firth and surrounding area, but detail in the Inner Sound was limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation